Hyaluronic Acid (800 kDa) Supplementation of University of Wisconsin Solution Improves Viability of Osteochondral Grafts and Reduces Matrix Metalloproteinase Expression during Cold Preservation - Takuya Yamada; Kentaro Uchida; Kenji Onuma; Gen Inoue; Jun Aikawa; Shotaro Takano; Hiroyuki Sekiguchi; Hisako Fujimaki; Masayuki Miyagi; Masashi Takaso (The Scientific World Journal)
Osteochondral allografting is a promising option for the treatment of large cartilage defects. However, because the cell viability of osteochondral tissues (OCTs) gradually reduces during storage at 4°C, methods for maintaining the cell viability of fresh OCTs are needed to improve transplantation outcomes. Here, we evaluated whether the supplementation of preservation solution with one of three different molecular weight forms of hyaluronic acid (HA) improved the viability of rat OCTs during long-term cold storage. The supplementation of University of Wisconsin (UW) solution with 800 kDa significantly improved the cell viability of OCT after 14 days at 4°C compared to nonsupplemented UW solution. In contrast, UW solution supplemented with either 1900 or 6000 kDa HA did not markedly improve the cell viability of the OCT. Real-time PCR analysis revealed that the levels of matrix metalloproteinases 2, 3, and 9 were significantly decreased in OCT stored in UW solution supplemented with 800 kDa HA. Although further studies in human OCT are warranted, these findings demonstrate that the use of 800 kDa HA in place of serum may be a suitable approach for the long-term preservation of osteochondral allografts designated for the repair of large cartilage defects in the clinical setting.